Exploration of Diversified Assessment Models for Business English Courses - Yue, Shuzhen (Journal of Global Economy, Business and Finance, 2024)
As one of the important courses in majors such as international trade and business management, the assessment method of Business English directly affects students' learning enthusiasm and the cultivation of practical application ability. The traditional single assessment method often focuses on the memorization of theoretical knowledge and test-taking skills, and ignores the assessment of students' practical application ability of Business English. Therefore, it is particularly important to explore diversified assessment models to comprehensively and objectively evaluate students' business English level. This paper aims to explore the construction and implementation of diversified assessment models for Business English courses. By analyzing the problems existing in the current assessment methods, this paper proposes the necessity, design principles and specific implementation strategies of diversified assessment models, in order to provide a reference for the teaching reform of Business English courses.